2020
DOI: 10.5812/aapm.110755
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the Third-Year Clinical Anesthesiology Residents Toward an Independent Clinical Practice Rotation in COVID-19 Pandemic in Iran

Abstract: Background: COVID-19 was a worldwide pandemic with international health emergencies and great challenges; health care personnel shortage and physician burnout is a potential major challenge that should be planned and managed; especially in those countries with a high COVID-19 occurrence. Objectives: This study was designed to assess the attitudes of 3rd-year anesthesiology residents toward an independent one month-length clinical care course for patients with COVID-19. Methods: A closed self-administered quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The results of this study regarding the crisis management/COVID-19 Pandemic demonstrated the role of curricular reform plans in these fields with a significant impact on the viewpoints of CA's (27,32,65).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results of this study regarding the crisis management/COVID-19 Pandemic demonstrated the role of curricular reform plans in these fields with a significant impact on the viewpoints of CA's (27,32,65).…”
Section: Discussionmentioning
confidence: 81%
“…Education Indices: Teaching method (23-25); Passing comprehensive exams (23,(26)(27)(28)(29); Mentorship (26,27); Assessment methods (24,28,29); Faculty development (30,31); Professionalism in medical education (28,32); Integration in education (31,(33)(34)(35); Crisis management (32); Competency-based medical education (study in progress).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical course of medical education in anesthesiology residency includes several "must need" items (14,24,25). ; similar to many other medical specialties (26,27), the current study included many of these basic items.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to assess the effects of the Repeated DOPS (R-DOPS) method on the performance of procedural skills in anesthesiology residents, DACC, SBMU in 6 months (May 2019-October 2019). To do so, the DOPS protocol was prepared based on the previous standard models for DOPS and the national curriculum for anesthesiology residents at the specialty level (7,8,10,14); then, the checklists were finalized for the examiners; including the following steps:…”
Section: Methodsmentioning
confidence: 99%
“…The lungs are the most affected organ because of the access of the virus to the host cells via the angiotensin-converting enzyme 2 (ACE-2) receptor (3,4). The virus destroys the alveolar-capillary tissue and causes edema, hemolysis, hemorrhage, and in some cases, superinfection (8). Endothelial damage through ACE-2 receptors leads to inflammation and coagulation cascade activation (5).…”
Section: Introductionmentioning
confidence: 99%